ANCIENT GRAMMARS: POPULARIZING LINGUISTICS HISTORIOGRAPHY ON INSTAGRAM - Kaltner, Leonardo Ferreira (2022)
This article is the result of a conference at the Abralin em Cena – Popularization of Linguistics event, held online, in 2021, by the Brazilian Association of Linguistics (Abralin). The text is linked to Grammaticography, the history of grammar, one of the lines of research of the Historiography of Linguistics (HL) (SWIGGERS, 2013; 2019), and has as its object of study the theme of the popularization of linguistics on Instagram, through the page Ancient Grammars. We divided our reflections into three thematic sections in the article: an introduction, to discuss the theoretical questions about the popularization of linguistics and Grammaticography, a second section, which describes the page and publications developed, and finally, the theoretical model used to to plan publications, which aims to disseminate studies on the history of linguistic thought in Brazil. Our theoretical fundamentals to debating the popularization of science, a general field that encompasses the popularization of linguistics, is the studies of interdiscursivity (MOTTA-ROTH; SCHERER, 2016).